The eight-item Morisky Medication Adherence Scale: validation of its Persian version in diabetic adults - Delara Laghousi; Fereshteh Rezaie; Mahasti alizadeh; Mohammad Asghari Jafarabadi (Babol University of Medical Sciences, 2021)
Background: Adherence to treatment is an important factor in the management of diabetic patients. The aim of this study was to examine the psychometric properties of the 8-item Morisky Medication Adherence Scale (MMAS-8) among type 2 diabetes. Methods: This study carried out in Family Medicine Clinics (FMCs) in Tabriz, North West of Iran from May to September 2018. A total of 320 patients suffering from Type 2 diabetes were included. Content and face validity of the Persian version of MMAS-8 ‎ were quantitatively evaluated. The Cronbachchr('39')s alpha and intra-class correlation (ICC) were calculated to assess the reliability. Exploratory factor analysis (EFA) was used to assess the construct validity of the questionnaire. Results: Content and face validity of the Persian version of MMAS-8 were confirmed. Good internal consistency (Cronbach's a = 0.83) and test-retest reliability (ICC= 0.87, P<0.001) were found. According to the results of the EFA, Persian version of MMAS-8 among diabetic patients had two dimensions: stopping to take medication due to the forgetfulness and for reasons other than forgetfulness. Conclusion: The Persian version of the MMAS-8 is a high valid and reliable questionnaire to screen medication adherence of Persian-speaking patients with diabetes.